Sub-0.3 volt amorphous metal WNx based NEMS switch with 8 trillion cycles - Abdulilah Mohammad Mayet; Mohammed Abdul Muqeet; Hala H. Alhashim; Fadi Kurdahi; Ehsan Eftekhari-Zadeh (Frontiers in Materials, 2024)
Introduction: The mechanical nature of nanoelectromechanical (NEM) switches makes them sluggish yet desirable for ultra-low-power, harsh environment applications. Two- and three-terminal NEM switches have been demonstrated using onedimensional, two-dimensional, and thin films, but sub-0.3 V operation with improved mechanical and electrical reliability is still elusive.Method: This study presents WNxnano-ribbon-based NEM sensor switches that operate at 0.6 V, 30 nanosecond switching time, 8 trillion cycles, and 0.5 mA ON current with less than 5 kΩ ON resistance, without stiction, mechanical welding, or short circuits. WNx’s high Young’s modulus gives it great elasticity and mechanical restoring force, which may overcome van der Waal and capillary forces.Results and Discussion: With its high Young’s modulus, the device’s nanoscale size facilitated low operating voltage. WNxnano-ribbon without grain boundaries is amorphous and more mechanically strong. Hammering and high current flow may destroy the nano-ribbon contact surface and interface, which is practically immaculate. Pull-out time (dominant delay factor) is 0 owing to high Young’s modulus, hence hysteresis loss and delay are absent. Elasticity and Young’s modulus increase speed.